The Role of Mathematics and Science Education in the Adult Offender Rehabilitation Process - Siphelele Mbatha; Halalisani Mngomezulu; Nonhlanhla Nduku; Onelisa Mbathu (E-Journal of Humanities, Arts and Social Sciences)
After the advent of democracy, the South African Department of Correctional Services implemented offender rehabilitation programmes as a means towards the humanistic approach to imprisonment, as opposed to the punishment approach. These programmes, even though not ostensible at first, were designed as the means for catalysing positive social behaviour, and for equipping offenders with the necessary skills to function in the work of skilled trade. The paper sought to explore, amongst the plethora of offender rehabilitation programmes, the role of mathematics and science education post-offender incarceration. From the pragmatic epistemological stance, qualitative and quantitative data were collected through semi-structured interviews and structured questionnaires, from four conveniently sampled ex-offenders. Framed within the QUANT-QUAL explanatory sequential mixed methods research design, and analysed thematically, through the lens of Vroom’s (1964) Expectancy Motivation Theory, the findings revealed that mathematics and science offender education does not significantly correlate with offenders’ ex-offenders’ employment prospects. The study also revealed an insignificant correlation between mathematics and science education and reduced recidivism. The researchers recommend the intervention from the South African legal; framework, to reduce ex-offenders’ criminal record duration so that their employment prospects will be broadened. The study presented in this intellectual piece will contribute to scholarship by situating mathematics and science learning within the ubiquitous offender rehabilitation cycle. The study will further aid in disseminating the unique role of offender mathematics and science education, particularly for scholars and policymakers whose focus is on offender rehabilitation in the democratic dispensation.